STEM Education: From Sputnik to Girl Scouts - Vaitekaitis, Jogaila (Acta Paedagogica Vilnensia, 2019)
The inconsistency of defining STEM (Science, Technology, Engineering, and Math) education is being addressed in this article. Seeing STEM education as having implications ranging from migration to workforce policies, it is vital to clarify its (inter)disciplinary structure and curriculum orientation. Using a literature review and analysis of documents, STEM education is being tracked from a post-sputnik era to more recent informal and private endeavors, revealing a multiplication of the STEM acronym and the diversification of its curriculum orientation. The findings confirm that there is no consensus on the exact scientific fields assigned to STEM, and the list of disciplines involved ranges from broad (including Social sciences, Humanities or Arts) to narrow (dominated by Natural and Formal sciences). The article implies that historical context and reforms in natural science education partly explain this inconsistency, as the subjects and their interdisciplinary relations are closely linked to overall curriculum orientation, which could be seen as cyclical in nature, swinging from child centered to labor market or subject centered curriculum, inviting to discuss modern science education not as singular STEM, but as plural STEMs viable to multiple pedagogical approaches, integration patterns and aims.